From Fibroadenoma to Phyllodes Tumor: Case Analysis of Borderline and Giant Breast Tumors with Literature Review - Kazlauskaitė, Justė; Schmeil, Iryna (Acta medica Lituanica, 2025)
Background: Phyllodes tumors are highly uncommon fibroepithelial neoplasms of the breast, accounting for less than 1% of all breast tumors. Differential diagnosis between phyllodes tumors and fibroadenomas by using imaging techniques such as ultrasound or mammography, as well as histological methods, can be challenging due to overlapping features. Phyllodes tumors are categorized into benign, borderline, and malignant types, each posing a different risk of recurrence and metastasis. Despite many advances in the imaging and biopsy techniques, diagnosing phyllodes tumors remains challenging. The purpose of this study is to review the existing literature on this topic and describe two cases of misdiagnosed phyllodes tumors.Materials and methods. A literature review was conducted by using the Medline (PubMed) database over 10 years. Information concerning the patients was sourced from the Uster Hospital database. After analyzing the cases of women with breast lumps from 2020 to 2023 in the Uster Hospital database, two cases of misdiagnosed phyllodes tumors were identified. These two cases were analyzed retrospectively.Results. A retrospective study of two cases confirms that phyllodes tumors are a rare phenomenon. A 51-year-old premenopausal woman presented with an 8 × 4 × 5 cm mass, initially diagnosed as a fibroadenoma. The final histopathology after surgical excision revealed a borderline phyllodes tumor with features overlapping those of a fibroadenoma. The second case involved a 59-year-old postmenopausal woman with a rapidly growing mass, which reached 11.9 × 11.3 cm and was initially diagnosed as a fibroadenoma but later confirmed as a borderline malignant phyllodes tumor with focal malignant components. Both cases highlight the limitations of imaging and core biopsy in accurately diagnosing phyllodes tumors and emphasize the need for comprehensive histopathological evaluation. The described clinical cases corresponded to the characteristics of phyllodes tumors indicated in the literature: they appeared in women older than 35 years, were hard to distinguish from fibroadenomas, and required surgical treatment.Conclusions. Phyllodes tumors are challenging to distinguish from fibroadenomas based on imaging and the initial biopsy results alone. Accurate diagnosis requires thorough histopathological examination following surgical excision. A multidisciplinary approach is essential for optimal management. Our cases show the complexity of phyllodes tumor diagnosis and the importance of considering phyllodes tumors in the differential diagnosis of breast masses, especially when clinical and imaging findings suggest a more aggressive pathology.
Keywords: phyllodes tumor; giant phyllodes tumor